ASUHAN KEPERAWATAN PADA NN. N DENGAN DISMENOREA DI WILAYAH SRENGSENG SAWAH JAKARTA SELATAN - Dhea Afisyah (2023)
Background: One of the problems experienced by women during menstruation is dysmenorrhea. Dysmenorrhea is a reproductive health disorder that makes more than 50% of women unable to carry out their activities for 1 to 3 days each month so they need time to rest. Primary dysmenorrhea occurs due to an imbalance of prostaglandins. Dysmenorrhea occurs by several risk factors such as menarche aged <12 years, lifestyle and being overweight. This research was conducted to determine dysmenorrhea and how to treat dysmenorrhea with nursing care for women who experience dysmenorrhea. Methods: This research was conducted using a case study method of nursing care at Ms. N with dysmenorrhea in the Srengseng Sawah area, South Jakarta on 22-24 February 2023. Data collection was through interviews, observation, physical examination and documentation. Results: The primary nursing diagnosis is acute pain associated with physiological injurious agents. Nursing interventions carried out include identifying the location, duration, quality and scale of pain, identifying factors that aggravate and relieve pain, provide non-pharmacological techniques to reduce pain, facilitate rest and sleep and teach non-pharmacological techniques to reduce pain. Implementation of nursing in accordance with nursing interventions that have been made and evaluate nursing. Within 3x24 hours the problem of acute pain can be resolved. Conclusion: The treatment that has been given to Ms. N based on nursing care can be resolved, Ms. N has not experienced dysmenorrhea, Ms. N already understands about dysmenorrhea and the treatment of dysmenorrhea.